2009
DOI: 10.1097/tp.0b013e3181bcde7b
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Tolerance to Collagen Type V Suppresses T-Helper-Cell-17 Lymphocyte-Mediated Acute Lung Transplant Rejection

Abstract: Background Rat lung allograft rejection is mediated by collagen type V (col(V)) specific Th17 cells. Adoptive transfer of these cells is sufficient to induce rejection pathology in isografts, whereas tolerance to col(V) suppresses allograft rejection. We therefore tested if regulatory T cells from tolerant rats could suppress the Th17 mediated rejection in the syngeneic model of lung transplantation. Methods Rats were subjected to syngeneic left lung transplantation and acute rejection was induced by adoptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 52 publications
1
32
0
3
Order By: Relevance
“…We and others (8,(12)(13)(14) previously reported that autoimmune responses to col(V) are linked to the pathogenesis of lung fibrosis. We also have previously reported IL-17-dependent anti-col(V) cellular immune responses in patients with OB with lung transplants (as measured by the trans-vivo delayed-type hypersensitivity assay); we attributed this response to be possibly due to the overabundance of induced ␣1(V) chains noted in the OB lesions (14).…”
Section: Il-17 Mediates Specific Rna and Protein Overexpression For Tmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others (8,(12)(13)(14) previously reported that autoimmune responses to col(V) are linked to the pathogenesis of lung fibrosis. We also have previously reported IL-17-dependent anti-col(V) cellular immune responses in patients with OB with lung transplants (as measured by the trans-vivo delayed-type hypersensitivity assay); we attributed this response to be possibly due to the overabundance of induced ␣1(V) chains noted in the OB lesions (14).…”
Section: Il-17 Mediates Specific Rna and Protein Overexpression For Tmentioning
confidence: 99%
“…Prior reports demonstrated that induction of tolerance to col(V) protects against OB mediated by col(V)-specific reactive Th17 cells, but the col(V) distribution in the clinical OB lesions has not been illustrated (13,53). Therefore, immunohistochemistry was utilized to determine the localization of col(V) in clinical OB.…”
Section: Col(v) Is Highly Expressed In Clinical Ob Lesions and In A Mmentioning
confidence: 99%
“…Advances in understanding the effects of allograft cellular senescence (accelerated ageing) on allograft function and BOS risk are needed, and a better understanding of the role of interleukin-17 [150][151][152][153][154][155][156], autoimmune pathways, regulatory lymphocyte populations [157][158][159][160][161][162][163] and neutrophil responses, as well as mechanisms by which the hypothetical phenomenon of epithelial-mesenchymal transition (which remains hypothetical and has not been well validated in humans) [164][165][166][167] leads to airway fibrosis, may lead to novel therapies to prevent and treat BOS. Improved animal models of OB are needed and are likely to be useful in improving our understanding of the role of these and other phenomena in the initiation, progression, prevention and treatment of OB following lung transplantation.…”
Section: Key Unanswered Questions and Specific Research Needsmentioning
confidence: 99%
“…Conventionally, Th1 cells and cytotoxic CD8 þ T cells induced by alloantigen stimuli were thought to be important in allograft rejection. However, recent studies provided evidence suggesting a role for IL-17 in acute allograft rejection, 14 and blockade of IL-17 action by an IL-17R/IgG-Fc fusion protein prolonged cardiac allograft survival. 15 Patients undergone acute renal or lung allograft rejection were also found to be associated with increased IL-17 in the serum or bronchoalveolar lavage.…”
mentioning
confidence: 99%